Efficacy of a continuous wound infiltration system for postoperative pain management in gynecologic patients who underwent single-port access laparoscopy for adnexal disease - Kang, Jun-Hyeok; Lee, Kyung A; Heo, Yae Rin; Kim, Woo Young; Paik, E Sun (Frontiers in Medicine, 2023)
Introduction: Single-port access (SPA) laparoscopy requires only one incision, unlike conventional laparoscopy. However, its umbilical incision is larger than that of conventional laparoscopy and can be vulnerable to postoperative pain. This study aimed to evaluate whether simultaneous use of a continuous wound infiltration (CWI) system and intravenous patient-controlled analgesia (IV PCA) effectively decreases surgical site pain in patients who underwent SPA laparoscopy due to gynecologic adnexal disease.Methods: A total of 371 patients who underwent SPA laparoscopy and who received IV PCA or CWI was retrospectively reviewed (combined group [CWI + IV PCA, n = 159] vs. PCA group [IV PCA only, n =212]). To evaluate postoperative pain management, the numeric rating scale (NRS) pain score after surgery, total amount of fentanyl administered via IV PCA, and additional pain killer consumption were collected.The NRS scores at 12 hours (1.90 ± 1.11 vs. 2.70 ± 1.08, p < 0.001) and 24 hours (1.82 ± 0.82 vs. 2.11 ± 1.44, p = 0.026) after surgery were significantly lower in the combined group than in the PCA group. The total amount of PCA fentanyl was significantly smaller in the combined group than in the PCA group (p < 0.001). The total quantity of rescue analgesics was smaller in the combined group than in the PCA group (p < 0.05).Combined use of the CWI system and IV PCA is an effective postoperative pain management strategy in patient who underwent SPA laparoscopy for adnexal disease.